2015
DOI: 10.1007/s00170-015-7459-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of grinding wheels impregnated with graphene nanoplatelets

Abstract: To provide the effective lubrication and thereby to reduce friction at the grinding wheel-work piece interface, resin-bonded grinding wheels impregnated with graphene nanoplatelets were developed. To study the impact of various physical characteristics of graphene nanoplatelets on the grinding performance, grinding wheels with varying graphene nanoplatelet concentrations (0.25, 0.5, 1, 2 and 4 wt%), surface areas (300, 500 and 750 mm 2 /g) and widths (5, 15 and 25 μm) were manufactured. Different aspects of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…Nanoparticles are added to CLF because of their high thermal conductivity and advanced tribological characteristics. CLF enriched with nanoparticles is characterized by changed heat conduction properties and different, in comparison with conventional cooling of the grinding zone, by heat exchange, reducing the phenomena of grinding energy dissipation and lowering the workpiece surface temperature [37][38][39].…”
Section: Antiadhesives and Lubricants In Solid Statementioning
confidence: 99%
“…Nanoparticles are added to CLF because of their high thermal conductivity and advanced tribological characteristics. CLF enriched with nanoparticles is characterized by changed heat conduction properties and different, in comparison with conventional cooling of the grinding zone, by heat exchange, reducing the phenomena of grinding energy dissipation and lowering the workpiece surface temperature [37][38][39].…”
Section: Antiadhesives and Lubricants In Solid Statementioning
confidence: 99%
“…The non-covalent functionalization process of GNP using CTAB was discussed elsewhere. 19 for preparation of nanocutting fluids. When the cutting fluid with GNP inclusions is used in MQL grinding, it is expected that the GNP adhere to the grinding surface and reduces the friction as one graphene sheet slides over the other.…”
Section: Gnpmentioning
confidence: 99%
“…MQL milling with nano grapheme-based cutting fluid has resulted in low initial flank wear as compared to both dry milling and MQL milling with pure cutting fluid. 18 Ravuri et al 19 observed a remarkable improvement of life of the grinding wheel and surface finish of Inconel 718 with grinding wheels impregnated with GNP.…”
Section: Introductionmentioning
confidence: 99%
“…The histogram shows that the minimum values of Espec can be achieved with the simultaneous use of chromium diiodide impregnated grinding wheel and the cooling lubricant, which consists of 5% aqueous solution of emulsion "Ukrinol-14" with the addition of 20 g/l of chromium diiodide. Apparently in this case, chromium diiodide, which is a part of lubricating and cooling technology, not only reduces the coefficient of friction in the area of contact of the abrasive grain with the processed material, but also contributes to the permanent restoration of chromium diiodide in the impregnated wheel [24][25][26][27][28][29][30][31].…”
Section: The Analysis Of Spectrogramsmentioning
confidence: 99%